Imaging β-Cell Function Using a Zinc-Responsive MRI Contrast Agent May Identify First Responder Islets - Thapa, Bibek; Suh, Eul Hyun; Parrott, Daniel; Khalighinejad, Pooyan; Sharma, Gaurav; Chirayil, Sara; Sherry, A. Dean (Frontiers in Endocrinology, 2022)
An imaging method for detecting beta-cell function in real-time in the rodent pancreas could provide new insights into the biological mechanisms involving loss of -cell function during development of type 2 diabetes and for testing of new drugs designed to modulate insulin secretion. In this study, we used a zinc-responsive MRI contrast agent and an optimized 2D MRI method to show that glucose stimulated insulin and zind secretion can be detected as functionally active “hot spots” in the tail of the rat pancreas. A comparison of functional images with histological markers show that insulin and zinc secretion does not occur uniformly among all pancreatic islets but rather that some islets respond rapidly to an increase in glucose while others remain silent. Zinc and insulin secretion was shown to be altered in streptozotocin and exenatide treated rats thereby verifying that this simple MRI technique is responsive to changes in beta-cell function.